2009
DOI: 10.1590/s1415-43662009000400004
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e produtividade agrícola de cana-de-açúcar em diferentes fontes de fósforo

Abstract: Com o objetivo de avaliar o crescimento e a produtividade agrícola da cana-planta em diferentes fontes de fósforo, conduziu-se um experimento de campo em Coruripe, AL, com 10 tratamentos: 1. Testemunha; 2. NK + micro; 3. Superfosfato simples (SS); 4. Superfosfato triplo (ST); 5. Fosmag; 6. Gafsa; 7. MAP; 8. Fórmula 06-26-24 (460 kg ha-1); 9. Composto e 10. SSP - parcelado. O delineamento estatístico foi em blocos ao acaso com 4 repetições. Avaliaram-se: população de perfilhos, altura de plantas, Índice de Área… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
1
24

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 13 publications
6
21
1
24
Order By: Relevance
“…Korndörfer & Melo (2009) observed a positive response in stalk production for localized phosphate fertilization, in which the dose of 100 kg ha -1 of P 2 O 5 promoted yields from 131.9 to 146.1 t ha -1 , varying according to the source used. The yield obtained in the present study is lower than that observed by many authors in experiments with plant cane (Santos et al, 2009;Calheiros et al, 2012). This probably occurred because the crop has undergone periods of low water availability in the months of March and April 2012 and from September 2012 until the harvest, in February 2013.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Korndörfer & Melo (2009) observed a positive response in stalk production for localized phosphate fertilization, in which the dose of 100 kg ha -1 of P 2 O 5 promoted yields from 131.9 to 146.1 t ha -1 , varying according to the source used. The yield obtained in the present study is lower than that observed by many authors in experiments with plant cane (Santos et al, 2009;Calheiros et al, 2012). This probably occurred because the crop has undergone periods of low water availability in the months of March and April 2012 and from September 2012 until the harvest, in February 2013.…”
Section: Resultscontrasting
confidence: 80%
“…Analysis of variance for number of tillers at 30 days after planting (DAP), stem diameter at 120 DAP, purity, fiber, corrected pol (CP), total recoverable sugar (TRS), ton of pol per hectare (TPH) and ton of sugarcane per hectare (TSH), as a function of phosphorus doses and forms of application on, there was no significant effect with respect to P doses and forms of application for this growth variable. Santos et al (2009), evaluating P sources on sugarcane growth in the municipality of Coruripe-AL, did not observe significant effect of different P sources on the number of tillers of the plant cane, although P is considered essential for tillering and root system growth in grasses, increasing their yields (Santos et al, 2002).…”
Section: Resultsmentioning
confidence: 82%
“…A redução progressiva na população de perfilhos dos 60 para os 240 DAC contrasta com o crescimento dos colmos para ambas as cultivares. Segundo Santos et al (2009), logo após o intenso período de perfilhamento (neste experimento observado até 60 DAC) e com a população já definida, iniciou-se a fase de alongamento do colmo.…”
Section: Resultsunclassified
“…Esta resposta pode ser relacionada ao fator capacidade de P na área experimental, que é reduzido, e à disponibilidade original de P no solo, classificada média (Alvarez et al, 1999;Santos et al, 2009). Para a classe de disponibilidade média a produção relativa esperada sem aplicação de fertilizante é de 70 a 90%; desta Estratégias que visam à maior eficiência dos fertilizantes fosfatados como granulação, aplicação localizada em linha ou cova e uso de fontes de menor solubilidade, apresentam maior efeito em condições menos favoráveis à absorção pela planta e mais favoráveis à adsorção e fixação do P pelo solo (Büll et al, 2004;Prochnow et al, 2006).…”
Section: Resultsunclassified
“…Para a classe de disponibilidade média a produção relativa esperada sem aplicação de fertilizante é de 70 a 90%; desta Estratégias que visam à maior eficiência dos fertilizantes fosfatados como granulação, aplicação localizada em linha ou cova e uso de fontes de menor solubilidade, apresentam maior efeito em condições menos favoráveis à absorção pela planta e mais favoráveis à adsorção e fixação do P pelo solo (Büll et al, 2004;Prochnow et al, 2006). Dentre as condições que favorecem a absorção do nutriente pela planta podem ser citados maior teor disponível, crescimento radicular abundante, solos com menor fator capacidade de P e níveis adequados de umidade (Bastos et al, 2008;Santos et al, 2009;Broggi et al, 2010).…”
Section: Resultsunclassified